[Baby trafficking ; Lisa Macuja ; Squatters [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
An investigative report on NBI uncovering a West German syndicate allegedly operating baby trafficking. Interview with Lisa Macuja. Looks at squatting syndicate.
Baby trafficking (19 min.) -- Lisa Macuja (13 min.) -- Squatters (16 min.)
VHS.
Keywords: Macuja, Lisa; Prostitution; Ballet dancers -- Philippines; Mail-order brides; Squatters -- Philippines